Articulaciones espacio-temporales en el cine brasileño de la Amazonía - Natalia Möller González (Centre de Recherches sur les Mondes Américains, 2019)
This article reviews the imaginary geographies and temporalities to which the representations of the Amazon in Brazilian cinema have been subjected. I suggest that this region has been mostly looked at from an outside perspective, which endows the space with a natural and remote character, while also relegating it to a primitive time, with indigenous people being depicted as constitutive part of nature and not as its agents. With an examination of the ethnographic film conventions that recreate imperial geographies as a starting point, I ask how some Brazilian films have understood the incorporation of indigenous people of the Amazon into the nation. In the last section, I analyze two films made by indigenous people of the Amazon within the framework of the Video project in the villages.